Uslub Khabari Bagi Terminologi Gegaran (zalzalah) Dalam Al-quran - Khairul Asyraf Mohd Nathir; Rosni Samah; Mohd Adi Amzar Mohammad Nawawi; Muhamad YazidAbdul Majid; Amani Nawi; Bushro Bakri (Usuli Faqih Research Center, 2024)
Indexed by MyCite